Veljavnost interneta kot anketnega orodja - Lozar Manfreda, Katja (Teorija in praksa, 2000)
Despite the 'non-coverage' problem the Internet is becoming a complement and/or alternative survey method. However, its validity, especially the convergent validity, needs to be established. The Internet surveying will become equivalent to other survey methods when proved that the survey errors are not larger than survey errors occuring by other survey methods. The paper presents some comparisons of Internet surveys with other survey methods and discusses their survey errors. A particular emphasis is placed on a comparison of a Web and mail survey, conducted as a part of project RIS at the Faculty of Social Sciences.
Keywords: Conducting an opinion poll; Internet; Methodology; Anketiranje; Metodologija; metode anketiranja; primerjava